Mechanical stimulus responsive 3D-Bio based graphene scaffolds for bone tissue engineering - Carvalho, Sara Diana Gomes (2021)
Bone tissue engineering has gained a high relevance in the past few years due to the potential to generate functional tissue. In bone tissue regeneration, there are several options that can be adopted, being the autologous bone replacement the preferential clinical procedure. However, the use of autologous materials has a drawback that consists of the limited quantity available in the body. As alternatives, significant efforts have been dedicated to developing synthetic materials for the incorporation in the patients to restore the form and function of the injured bone. This work focus on the development of biomaterials for bone regeneration, which must possess relevant specific biological characteristics to be incorporated into the human body. They must mimic the function and structure of the bone extracellular matrix (ECM), in order to provide a three-dimensional (3D) environment capable of improving cellular adhesion, proliferation and differentiation, as well as presenting adequate biophysical and biochemical characteristics to induce and potentiate the bone tissue regeneration. Currently, biomaterials obtained from natural sources are promising options for application in tissue engineering due to their good biological performance. In this work, it was reported for the first time the self-assembly of graphene oxide (GO) nanosheets on the natural spongin skeleton by the layer-by layer (LbL) method. These improved mechanical and biological properties of the MS make it a very relevant candidate to explore as a template for the development of new biomimetic scaffolds with appropriate structural and biochemical cues for bone cells. Firstly, this work was dedicated to the MS purification regarding the removal of some anatomic constituents or contaminants. The chemical composition, structure and mechanical properties of MS were accessed, by FTIR, SEM and mechanical compression tests. The preparation of the bionanocomposites was performed by exploring the self-assembly of GO on the surface of MS using different positive polyelectrolytes (PDDA and PEI). The obtained results showed that the multilayer deposition PEI/GO gives rise to highly efficient surface functionalization of MS. These hybrids materials showed a high mechanical and thermal stability, which allows the preparation of two sets of samples, with reduced(rGO) and non-reduced GO, for the development of biological studies. The in vitro studies performed with osteoblasts under dynamic conditions revealed that the bionanocomposites prepared with GO showed an improved performance in terms of cell viability and mineralization. These results can be mainly attributed to the fact that GO presents more oxygen functional groups in its composition than the samples with rGO. These bionanocomposites were able to promote cell adhesion and proliferation, and more importantly guaranty their structural integrity of during the dynamic test.